The e-commerce market development of China as the biggest in the world and Alibaba as a successful model of a market platform during the year 2015 - Hidalgo Naranjo, Doménica Solange (2018)
In 2013, China became the biggest e-commerce market worldwide, where Alibaba has consolidated itself as the biggest company of the market. This is an exploratory study aimed to present an updated overview of the Chinese e-commerce state, and for this purpose, focused on the year 2015. Through an inductive research method, this investigation aims to analyze how the particular conditions that will be considered have contributed to the current development that the e-commerce industry has reached in China. The role of the political and economic environment is established as it influences the business scenario that the country provides for the e-commerce market. Alibaba's business model is analyzed in order to identify the implemented strategies that let it reach its current success. The theoretical foundation of this investigation is based in the concepts provided by Michael Porter to the Positioning School and the Strategic Management field. The hypothesis formulated for this investigation is "China’s economic reform oriented towards foreign investment and the rapid spreading of internet would favor the establishment of new companies such as Alibaba, which has currently gained an omnichannel presence in the e-tail market by implementing innovative strategies as a multisided platform". The main findings show that China's economic reform in 1979 established the basis for its outstanding growth, becoming the second biggest economy worldwide and the rapid internet expansion that took place during the last decade was a key factor for the development of the e-commerce industry. Alibaba's success has been determined by a correct identification of the customers' needs and a rapid response to market tendencies, implementing cost-leadership and differentiation strategies throughout the different stages. Among the most relevant tendencies identified can be mentioned the consolidation of mobile phones as the principal internet access, online payments, and marketing channel, the influence of social media over customers, the importance of special buying occasions, such as Single's Day, and the potential that an omnichannel approach presents for the next years.